Possibilities and prospects of using biofluorescent proteins at the stage of preclinical evaluation of live vaccines, using the example of the Yersinia pestis vaccine strain EV NIIEG pTURBOGFP-B - Svetlana N. Klyueva; Angelina A. Budanova; Aleksandr L. Kravtsov; Svetlana A. Bugorkova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Introduction. Currently, studies aimed at finding the most informative and optimized method for assessing the survival rate of the plague microbe vaccine strain in the body of animals vaccinated against plague are relevant.